Geologic atlas of Pope County, Minnesota, C-15, Part B, Plate 9, Sensitivity to Pollution of the Buried Aquifers (Minnesota Geological Survey, 2642 University Avenue, St. Paul Minnesota 55114)
0f5e97259f2672296b8d431ff21b5e4a
United States
Minnesota
Pope
0f5e97259f2672296b8d431ff21b5e4a
Map showing the susceptibility of ground water in the buried unconsolidated sediment aquifers to contamination, including the age of the water as determined from radioactive isotopes in the water, scale 1:150,000, Pope County. Electronic file available at: ftp://mgssun6.mngs.umn.edu/map_catalog/pdf/umn22353.pdf
Keywords: Surface geology; bedrock geology and hydrogeology of Pope County; Environment